Teachers’ Social-Emotional Competence in Local Wisdom: An In-Depth View from Adabul Mua'llimin by Ibn Sahnun - Yahya, Yuniar Indra; Muhamad, Norhisham (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
Teacher competence in modern education extends beyond pedagogical and subject mastery to encompass social-emotional dimensions, as emphasized in frameworks like CASEL. However, such competencies are not novel but are deeply rooted in local wisdom and classical pedagogical traditions. This study examines the alignment between the social-emotional competencies of teachers and the principles outlined in Ibn Sahnun’s 9th-century work, Adabul Mu'allimin, using the five-component SEL framework: Self-Awareness, Self-Management, Social Awareness, Relationship Skills, and Responsible Decision-Making. Through qualitative thematic analysis of the text, the research identifies and maps Ibn Sahnun’s ethical guidelines for teachers to these SEL components. Findings reveal that the text strongly emphasizes Self-Management, particularly in emotional regulation, integrity, and professional conduct, while also integrating Self-Awareness, Social Awareness, Relationship Skills, and Responsible Decision-Making. The study concludes that core SEL concepts are not recent innovations but are integral to classical Islamic educational ethics, offering a culturally and spiritually relevant model for teacher development. This bridges contemporary SEL theory with traditional Islamic pedagogy, providing an alternative framework for enhancing teachers' social-emotional competence within Islamic educational contexts.